THE ENGLISH TUTORS’ STRATEGIES TO IMPROVE STUDENTS VOCABULARIES - Nuriska Alfira Husna (Nusantara Hasana Journal, 2024)
Vocabulary is a set of familiar words in one's language. Vocabulary, usually developed with age, serves as a useful and fundamental tool for communication and acquiring knowledge. Teaching-learning strategies are general patterns of student-teacher actions in realizing teaching and learning activities. The definition of strategy in this case shows the abstract characteristics of student-teacher actions in certain actual learning events. In this study, researchers used a qualitative approach. Researchers conducted research on 6 tutors who taught at the tutoring. on collecting data from 6 English tutors with 27 questions of interviews. Here are some strategies that are widely used in teaching student vocabulary, namely: expository, games as review, repetition and interaction, jigsaw and tpr.